The impact of wind on the rainfall–runoff relationship in urban high-rise building areas - X. Gao (Copernicus Publications, 2021)
Wind drift has a significant influence on the rainfall–runoff relationship in urban high-rise building areas since the oblique rainfall caused by the wind drift can interact with the building walls. However, the impact of the rainfall inclination angle on the rainfall–runoff process in urban high-rise building areas has not been studied. In this study, the relationship between wind and the rainfall–runoff process in such areas was explored. A theoretical framework has been developed to describe their relationship, including a computational fluid dynamics (CFD) method to obtain the relationship between wind speed and rainfall inclination and a newly derived equation to describe the relationship between rainfall inclination and the runoff coefficient. Subsequently, a laboratory scale model experiment was conducted to verify the proposed framework. The main results are that (1) the runoff coefficient calculated by the proposed theoretical framework is highly consistent with that obtained from the laboratory experiment, (2) the runoff coefficient of urban high-rise building areas increases with wind speed and the increase rate is linear with the tangent of the rainfall inclination angle, and (3) the change in the runoff coefficient for the experiment with larger raindrop is 0.047 when the wind speed increases from 0 to 5.9 m s−1, while that for the experiment with smaller raindrop is 0.064, which means that the rainfall with larger droplets is less influenced by the wind.